The Market of Biopharmaceutical Medicines: A Snapshot of a Diverse Industrial Landscape - Moorkens, Evelien; Meuwissen, Nicolas; Huys, Isabelle; Declerck, Paul; Vulto, Arnold G.; Simoens, Steven (Frontiers in Pharmacology, 2017)
Background: Biopharmaceutical medicines represent a growing share of the global pharmaceutical market, and with many of these biopharmaceutical products facing loss of exclusivity rights, also biosimilars may now enter the biopharmaceutical market. Objectives: This study aims to identify and document which investment and development strategies are adopted by industrial players in the global biopharmaceutical market. Methods: A descriptive analysis was undertaken of the investment and development strategies of the top 25 pharmaceutical companies according to 2015 worldwide prescription drug sales. Strategies were documented by collecting data on manufacturing plans, development programs, acquisition and collaboration agreements, the portfolio and pipeline of biosimilar, originator and next-generation biopharmaceutical products. Data were extracted from publicly available sources. Results: Various investment and development strategies can be identified in the global biopharmaceutical market: a) development of originator biopharmaceuticals, b) investment in biotechnology, c) development of next-generation biopharmaceuticals, d) development of biosimilars, e) investment in emerging countries, and f) collaboration between companies. In the top 25 pharmaceutical companies almost every company invests in originator biopharmaceuticals and in biotechnology in general, but only half of them develops next-generation biopharmaceuticals. Furthermore, only half of them invest in development of biosimilars. The companies’ biosimilar pipeline is mainly focused on development of biosimilar monoclonal antibodies and to some extent on biosimilar insulins. A common strategy is collaboration between companies and investment in emerging countries. Conclusions: A snapshot of investment and development strategies used by industrial players in the global biopharmaceutical market shows that all top 25 pharmaceutical companies are engaged in the biopharmaceutical market and that this industrial landscape is diverse. Companies do not focus on a single strategy, but are involved in multiple investment and development strategies. A common strategy to market biopharmaceuticals is collaboration between companies. These collaborations can as well be used to gain access in regions the company has less experience with. With patents expiring for some of the highest selling monoclonal antibodies, this snapshot highlights the interest of companies to invest in the development of these molecules and/or enter into collaborations to create access to these molecules.